Incidence, prevalence and risk factors for low back pain in adolescent athletes: a systematic review and meta-analysis - Wall, J.; Meehan, W. P.; Trompeter, K.; Gissane, C.; Mockler, D.; van Dyk, N.; Wilson, F. (British Journal of Sports Medicine, 2022)
Objective: To investigate the incidence, prevalence, risk factors and morphological presentations of low back pain (LBP) in adolescent athletes.